Feeding Asian honeybee queens with European honeybee royal jelly alters body color and expression of related coding and non-coding RNAs - Abdelmawla, Amal; Yang, Chen; Li, Xin; Li, Mang; Li, Chang Long; Liu, Yi Bo; He, Xu Jiang; Zeng, Zhi Jiang (Frontiers in Physiology, 2023)
Abstract: The Asian honeybee (Apis cerana) and the European honeybee (Apis mellifera) are two different species with reproductive isolation. Previous studies reported that exchanging the larval food, known as nutritional crossbreed, resulted in obvious changes in morphology, physiology and behavior. This study explored the molecular mechanisms underlying the honeybee nutritional crossbreed. we used full nutritional crossbreed technology by rearing A. cerana queens by feeding them with an A. mellifera royal jelly-based diet in an incubator, and subsequently compared the body color and the expression of genes, microRNA, lncRNA, and circRNA among nutritional crossbreed A. cerana queens (NQ), and control A. cerana queens (CQ). Our results showed that the NQ’s body color turned yellow compared to the black control queens. Whole RNA sequencing results showed that a total of 1484, 311, 92, and 169 DEGs, DElncRNAs, DEmiRNAs, and DEcircRNAs, respectively, were identified in NQ and CQ, in which seven DEGs were enriched for three key pathways (tryptophan, tyrosine, and dopamine) that are involved in melanin synthesis. Interestingly, eight DElncRNAs and three DEmiRNAs were enriched into the key pathways regulating the above key DEGs. No circRNAs were enriched into these key pathways. Knocking down two key genes (KMO and TPH1) resulted in altered body color, confirming the function of key DEGs in the regulation of honeybee body color. These findings reveal that the larval diets from A. mellifera could change the body color of A. cerana, possibly by altering the expression of non-coding RNAs and related key genes. This study serves as a model of epigenetic regulation in insect body color induced by environmental factors. Keywords: Honeybees; nutritional crossbreed; body color alteration; gene expression; non-coding RNA expression